X-ray eruptions every 22 days from the nucleus of a nearby galaxy - Guolo, M.; Pasham, D.R.; Zajaček, M.; Coughlin, E.R.; Gezari, S.; Suková, P.; Wevers, T.; Witzany, V.; Tombesi, F.; van Velzen, S.; Alexander, K.D.; Yao, Y.; et al. (2024)
Galactic nuclei showing recurrent phases of activity and quiescence have recently been discovered. Some have recurrence times as short as a few hours to a day and are known as quasi-periodic X-ray eruption (QPE) sources. Others have recurrence times as long as hundreds to a thousand days and are called repeating nuclear transients. Here we present a multiwavelength overview of Swift J023017.0+283603 (hereafter Swift J0230+28), a source from which repeating and quasi-periodic X-ray flares are emitted from the nucleus of a previously unremarkable galaxy at ∼165 Mpc. It has a recurrence time of approximately 22 days, an intermediary timescale between known repeating nuclear transients and QPE sources. The source also shows transient radio emission, likely associated with the X-ray emission. Such recurrent soft X-ray eruptions, with no accompanying ultraviolet or optical emission, are strikingly similar to QPE sources. However, in addition to having a recurrence time that is ∼25 times longer than the longest-known QPE source, Swift J0230+28’s eruptions exhibit somewhat distinct shapes and temperature evolution compared to the known QPE sources. Scenarios involving extreme mass ratio inspirals are favoured over disk instability models. The source reveals an unexplored timescale for repeating extragalactic transients and highlights the need for a wide-field, time-domain X-ray mission to explore the parameter space of recurring X-ray transients.